2007
DOI: 10.1051/0004-6361:20066645
|View full text |Cite
|
Sign up to set email alerts
|

The “666” collaboration on OGLE transits

Abstract: Transiting planets are essential to study the structure and evolution of extra-solar planets. For that purpose, it is important to measure precisely the radius of these planets. Here we report new high-accuracy photometry of the transits of OGLE-TR-10 and OGLE-TR-56 with VLT/FORS1. One transit of each object was covered in Bessel V and R filters, and treated with the deconvolution-based photometry algorithm DECPHOT, to ensure accurate millimagnitude light curves. Together with earlier spectroscopic measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 25 publications
4
60
2
Order By: Relevance
“…Therefore, the estimates for the decrease in the orbital period due to orbital decay range from 0.1 to 10 ms yr −1 . This value is only a few times smaller than the current error on the orbital period (86 ms from Pont et al 2007). …”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, the estimates for the decrease in the orbital period due to orbital decay range from 0.1 to 10 ms yr −1 . This value is only a few times smaller than the current error on the orbital period (86 ms from Pont et al 2007). …”
Section: Introductionmentioning
confidence: 53%
“…In Section 2, we describe the collection and analysis of the data. In Section 3, we describe the transit model fitting; we note the difference in light curve shape compared to the light curve published by Pont et al (2007) in Section 3.3. In Section 4, we present the revised transit ephemeris and discuss how the timing constrains the presence of other objects in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clearly demonstrated that the luminosity in transiting systems can be very well constrained by the LC fitting (Pont et al 2007;Sozzetti et al 2007). However, for CoRoT-7 the shallow transit and the stellar activity result in a large uncertainty on the stellar density and further on the planet radius, so we have abandoned it.…”
Section: Mass Radius and Effective Temperaturementioning
confidence: 99%
“…It was used several times in the past to obtain high-precision transit photometry (e.g. Gillon et al 2007bGillon et al , 2009aPont et al 2007). The high-resolution mode and 1×1 binning were used to optimize the spatial sampling, resulting in a 4.6 × 4.6 field of view with a pixel scale of 0.063 /pixel.…”
Section: Vlt/fors2 Transit Photometrymentioning
confidence: 99%